Data from: From tissue to silicon to plastic: three-dimensional printing in comparative anatomy and physiology - Lauridsen, Henrik; Hansen, Kasper; Nørgård, Mathias Ø.; Wang, Tobias; Pedersen, Michael (Zenodo, 2016)
Comparative anatomy and physiology are disciplines related to structures and mechanisms in three-dimensional (3D) space. For the past centuries, scientific reports in these fields have relied on written descriptions and two-dimensional (2D) illustrations, but in recent years 3D virtual modelling has entered the scene. However, comprehending complex anatomical structures is hampered by reproduction on flat inherently 2D screens. One way to circumvent this problem is in the production of 3D-printed scale models. We have applied computed tomography and magnetic resonance imaging to produce digital models of animal anatomy well suited to be printed on low-cost 3D printers. In this communication, we report how to apply such technology in comparative anatomy and physiology to aid discovery, description, comprehension and communication, and we seek to inspire fellow researchers in these fields to embrace this emerging technology. Ambystoma tigrinum_head Interactive PDF model of Ambystoma tigrinum head. To activate the 3D feature click the model. Using the cursor it is now possible to rotate, zoom, pan the model and in the model tree all segments of the model can be turned on/off or made transparent. Ambystoma tigrinum_C2_1100% Ready to 3D print STL file of Ambystoma tigrinum C2 (axis). Bitis arietans_head Interactive PDF model of Bitis arietans head. To activate the 3D feature click the model. Using the cursor it is now possible to rotate, zoom, pan the model and in the model tree all segments of the model can be turned on/off or made transparent. Bitis arietans_C2_950% Ready to 3D print STL file of Bitis arietans C2 (axis). Gadus morhua_head Interactive PDF model of Gadus morhua head. To activate the 3D feature click the model. Using the cursor it is now possible to rotate, zoom, pan the model and in the model tree all segments of the model can be turned on/off or made transparent. Gadus morhua_C2_400% Ready to 3D print STL file of Gadus morhua C2 (axis). Galeorhinus galeus_head Interactive PDF model of Galeorhinus ...